Pengembangan Game Edukasi Sejarah Perebutan Gudang Don Bosco Berbasis Narasi Menggunakan Interactive Digital Narrative - Rifki Riza Alfiansyah; Pratama Wirya Atmaja; Andreas Nugroho Sihananto (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
The development of technology has facilitated easy access to information through the internet. Nevertheless, many students are still less interested in studying Indonesian history. To capture the interest of current students, integrating learning methods with gaming is a step that can be taken. The aim of this research is to create an interactive narrative-based educational game that conveys knowledge about the historical battle in Surabaya, specifically the Don Bosco warehouse raid. This study uses the Unified Modeling Language (UML) model and the Interactive Digital Narrative (IDN) development method as the framework and foundation for writing interactive storytelling narratives, resulting in a gaming application that is both enjoyable and educational. Based on Likert scale testing, this educational game application provides insights into the history of the Don Bosco warehouse raid with a score of 3.65 on the Likert scale.